![\sqrt{14 + 6 \sqrt{5} } = a + \sqrt{b \:} \: then \: find \: b {?}^{2} - a {?}^{2} \sqrt{14 + 6 \sqrt{5} } = a + \sqrt{b \:} \: then \: find \: b {?}^{2} - a {?}^{2}](https://tex.z-dn.net/?f=+%5Csqrt%7B14+%2B+6+%5Csqrt%7B5%7D+%7D++%3D+a++%2B++%5Csqrt%7Bb+%5C%3A%7D++%5C%3A+then+%5C%3A+find+%5C%3A+b+%7B%3F%7D%5E%7B2%7D++-+a+%7B%3F%7D%5E%7B2%7D+)
This is the question, please answer with the whole solution...
Answers
Answered by
0
Answer:
-4
Step-by-step explanation:
Given :
√14 + 6√5
=> √9 + 5 + 6√5 = a + √b
=> √3² + (√5)² + 2 * 3√5 = a + √b
[∵ a² + b² + 2ab = (a + b)²]
=> √(3 + √5)² = a + √b
=> 3 + √5 = a + √b
Thus,
a = 3, b = √5
Then,
b² - a² = (√5)² - (3)²
= 5 - 9
= -4
Hope it helps!
Similar questions